If it's not what You are looking for type in the equation solver your own equation and let us solve it.
D( x )
2*x+1 = 0
10*x+5 = 0
2*x+1 = 0
2*x+1 = 0
2*x+1 = 0 // - 1
2*x = -1 // : 2
x = -1/2
10*x+5 = 0
10*x+5 = 0
10*x+5 = 0 // - 5
10*x = -5 // : 10
x = -5/10
x = -1/2
x in (-oo:-1/2) U (-1/2:+oo)
4/(10*x+5)+2/5 = 7/(2*x+1) // - 7/(2*x+1)
4/(10*x+5)-(7/(2*x+1))+2/5 = 0
4/(10*x+5)-7*(2*x+1)^-1+2/5 = 0
4/(10*x+5)-7/(2*x+1)+2/5 = 0
(4*5*(2*x+1))/(5*(10*x+5)*(2*x+1))+(-7*5*(10*x+5))/(5*(10*x+5)*(2*x+1))+(2*(10*x+5)*(2*x+1))/(5*(10*x+5)*(2*x+1)) = 0
4*5*(2*x+1)-7*5*(10*x+5)+2*(10*x+5)*(2*x+1) = 0
40*x^2-310*x+40*x-155+10 = 0
40*x^2-270*x-145 = 0
40*x^2-270*x-145 = 0
5*(8*x^2-54*x-29) = 0
8*x^2-54*x-29 = 0
DELTA = (-54)^2-(-29*4*8)
DELTA = 3844
DELTA > 0
x = (3844^(1/2)+54)/(2*8) or x = (54-3844^(1/2))/(2*8)
x = 29/4 or x = -1/2
5*(x+1/2)*(x-29/4) = 0
(5*(x+1/2)*(x-29/4))/(5*(10*x+5)*(2*x+1)) = 0
(5*(x+1/2)*(x-29/4))/(5*(10*x+5)*(2*x+1)) = 0 // * 5*(10*x+5)*(2*x+1)
5*(x+1/2)*(x-29/4) = 0
( x+1/2 )
x+1/2 = 0 // - 1/2
x = -1/2
( x-29/4 )
x-29/4 = 0 // + 29/4
x = 29/4
x in { -1/2}
x = 29/4
| -3/7z+4/7z=-1/7-5/7 | | 9x+60=9x+60 | | 8.5x+3=3x+5 | | 7a=2(1a-10) | | 4x-8=5x+15 | | 6x+y=-14 | | -1/2+X+2/3=5/6 | | 17b+4=-4/1/4 | | 4(x+3)-10=18 | | -2v=1/3 | | 5/x+3/x | | 6x/x-1=4 | | -30=x-100 | | 5x-(x-10)=3x-(5x-6) | | 4x-3x=11 | | 30=x-100 | | M-15m= | | -14602=x-16215 | | 9(x+6)+6= | | -2k-4=16 | | 14602=x-16215 | | 250+9p=450 | | 412x+52=823 | | x-16215=14602 | | 0.4+0.3y=1 | | 34-10w=6w | | 5x=5x | | 4.3+0.4x=0.7 | | 8x+4=10x-20 | | 10x+7=23 | | 1/2h-5=9 | | 0.1y=0.2 |